Bioceramic materials - Emerenciano Bueno, Carlos Roberto [UNESP]; Angelo Cintra, Luciano Tavares [UNESP]; Benetti, Francine [UNESP]; Dal Fabbro, Renan [UNESP]; De Castilho Jacinto, Rogério [UNESP]; Dezan-Júnior, Elói [UNESP] (My University, 2019)
Biomaterials are conceptualized as natural or synthetic materials used in contact with biological systems with the purpose of repairing or replacing lost hard or soft tissue. Ceramics are inorganic materials made by the heating of raw materials. Thus, the term bioceramics refers to biocompatible ceramic materials, preferential not only bio-inert, but with bioactive characteristics and the ability to stimulate repair on soft and hard tissues. Bioinert ceramics, as alumina and zirconia, are used for prosthetic reasons, due to its elevated resistance. Bioactive ceramics have a larger indication, classified according to its main component into calcium silicate cements (mineral trioxide aggregate), bioactive glass, calcium phosphates (hydroxyapatite, β-tricalcium phosphates, biphasic phosphates) and silicate based sealers. In dentistry, bioceramics are mainly used in periodontology and in implantodontology as bone filling material, because its osteoinductivity ability. More recently, bioceramics are being added to implant surfaces to enhance osteointegration. Since bioceramic materials applications were introduced in the endodontics field, its hydraulic characteristics allows a wide variety of use, making this a choice material for bone defects, pulpotomy, retrograde filling, apexificaton, revascularization, root perforations and, more recently, as an obturating endodontic sealer. This chapter discuss the main bioceramics used in dentistry, encompassing composition, properties, mechanism of action, applications and advantages, along with future perspectives.
Keywords: Bioactive materials; Bioceramics; Biomaterials; Odontology